Prevalence of Elevated Alanine Aminotransferase by Diagnostic Criterion, Age, and Gender among Adolescents - Jing Zhang; Zheng-Ying Wang; Jing-Ping Zhang; Hua Zhou; Zan Ding (Gastroenterology Research and Practice)
Background. Serum alanine aminotransferase (ALT) activity was measured not only to detect liver disease, but also to monitor overall health. The purpose of this study was to obtain the prevalence of elevated ALT levels among adolescents. Methods. In a school-based cross-sectional study, a representative sample was analyzed from 9 middle and high schools in Shenzhen, China, during 2017 to 2018. Elevated ALT was defined as diagnostic criterion I (>30 U/L for boys and >19 U/L for girls) and diagnostic criterion II (>40 U/L). Results. From the adolescent population, a total of 7281 students (boys, 4014, and girls, 3267) aged from 10 to 17 years were collected. The prevalence of elevated ALT was 7.11% (6.88% for boys and 7.41% for girls) by criterion I and 2.72% (3.96% for boys and 1.19% for girls) by criterion II. Based on the Shenzhen census and Chinese national census population, the adjusted prevalence of elevated ALT was 7.65% (boys 7.19% and girls 8.21%) and 6.79% (boys 6.07% and girls 7.56%) by criterion I and 2.85% (boys 4.20% and girls 1.16%) and 2.43% (boys 3.49% and girls 1.29%) by criterion II. For age, the overall trends were increasing progressively, regardless of the use of diagnostic criteria for an elevated ALT activity. Conclusions. This study supplements the gap that the prevalence of elevated ALT levels differed in gender, age, and criteria among adolescents of Shenzhen. We should take the prevalence as a predictor and continue to play a warning and preventive role in preparation for further intervention.